Proposition of a hybrid price index formula for the Consumer Price Index measurement - Białek, Jacek (Equilibrium. Quarterly Journal of Economics and Economic Policy, 2020)
Research background: The Consumer Price Index (CPI) is a basic, commonly accepted and used measure of inflation. The index is a proxy for changes in the costs of household consumption and it assumes constant consumer utility. In practice, most statistical agencies use the Laspeyres price index to measure the CPI. The Laspeyres index does not take into account movements in the structure of consumption which may be consumers' response to price changes during a given time interval. As a consequence, the Laspeyres index can suffer from commodity substitution bias. The Fisher index is perceived as the best proxy for the COLI but it needs data on consumption from both the base and research period. As a consequence, there is a practical need to look for a proxy of the Fisher price index which does not use current expenditure shares as weights. Purpose of the article: The general purpose of the article is to present a hybrid price index, the idea of which is based on the Young and Lowe indices. The particular aim of the paper is to discuss the usefulness of its special case with weights based on correlations between prices and quantities. Methods: A theoretical background for the hybrid price index (and its geometric version) is constructed with the Lowe and Young price indices used as a starting point. In the empirical study, scanner data on milk, sugar, coffee and rice are utilized to show that the hybrid index can be a good proxy for the Fisher index, although it does not use the expenditures from the research period. Findings & Value added: The empirical and theoretical considerations con-firm the hybrid nature of the proposed index, i.e. in a special case it forms the convex combination of the Young and Lowe indices. This study points out the usefulness of the proposed price index in the CPI measurement, especially when the target index is the Fisher formula. The proposed general hybrid price index formula is a new one in the price index theory. The proposed system of weights, which is based on the correlations between prices and quantities, is a novel idea in the price index methodology.